Future generations and international law - Agius, Emmanuel; Busuttil, Salvino ([S.l.] : Routledge, 2009)
Sustainable development requires consideration of the quality of life that future generations will be able to enjoy, and as the adjustment to sustainable lifestyles gathers momentum, the rights of future generations and our responsibility for their wellbeing is becoming a central issue. In this, the first book to address this emerging area of international law, leading experts examine the legal and theoretical frameworks for representing and safeguarding the interests of future generations in current international treaties. This unique volume will be required reading for academics and students of international environmental law and policy. Emmanuel Agius is Senior Lecturer at the Faculty of Theology and Coordinator of the Future Generations Programme at the Foundation for International Studies, University of Malta. Salvino Busuttil is former Director General of the Foundation for International Studies. Future Generations and International Law is the seventh volume in the International Law and Sustainable Development series, co-developed with FIELD. The series aims to address and define the major legal issues associated with sustainable development and to contribute to the progressive development of international law. Other titles in the series are: Greening International Law, Interpreting the Precautionary Principle, Property Rights in the Defence of Nature, Improving Compliance with International Environmental Law, Greening International Institutions and Quotas in International Environmental Agreements. 'A legal parallel to the Blueprint series - welcome, timely and provocative' David Pearce Originally published in 1997.
Keywords: Environmental law, International; International law; Sustainable development--Law and legislation